Technical feasibility proof for high-resolution low-dose photon-counting CT of the breast - Kalender, Willi Alfred; Kolditz, Daniel; Steiding, Christian; Ruth, Veikko; Lück, Ferdinand; Rossler, Ann-Christin; Wenkel, Evelyn (European Radiology, 2017)
X-ray computed tomography (CT) has been proposed and evaluated multiple times as a potentially alternative method for breast imaging. All efforts shown so far have been criticized and partly disapproved because of their limited spatial resolution and higher patient dose when compared to mammography. Our concept for a dedicated breast CT (BCT) scanner therefore aimed at novel apparatus and detector design to provide high spatial resolution of about 100 ?m and average glandular dose (AGD) levels of 5 mGy or below. Photon-counting technology was considered as a solution to reach these goals. The complete concept was previously evaluated and confirmed by simulations and basic experiments on laboratory setups. We here present measurements of dose, technical image quality parameters and surgical specimen results on such a scanner. For comparison purposes, the specimens were also imaged with digital mammography (DM) and breast tomosynthesis (BT) apparatus. Results show that photon-counting BCT (pcBCT) at 5 mGy AGD offers sufficiently high 3D spatial resolution for reliable detectability of calcifications and soft tissue delineation.o Photon-counting detector technology allows for spatial resolution better than 100 ?m. o pcBCT allows for dose levels in the screening mammography range. o pcBCT provides the highest quality imaging of microcalcifications.
EVALuna2:14668